Toward Understanding Another Gender Gap: How Women in Economic Development Perceive Access to Capital. (2nd October 2017) - Read, Dustin C.; Leland, Suzanne M.
ABSTRACT: This study uses survey data collected from members of the International Economic Development Council (IEDC) to assess gender differences in the perceptions of female economic developers involved in the policy process. The analysis reveals women are more likely than their male counterparts to believe access to capital serves as a barrier to economic development in the communities they serve. This finding is important because bureaucratic perceptions are anticipated to have a gendered dimension, because there is ample evidence that women-owned businesses less frequently obtain external financing than do those owned by men. This obstacle to growing a business may therefore resonate more strongly with female economic developers if their perceptions reflect experiences and socialization processes shared with the women they represent. Results of an ordinal logistic regression model support this contention and contribute to the study of economic development and the role of women in the policy process.